KARAKTERISTIK MORFOLOGI, PERTUMBUHAN IN VITRO DAN KEMAMPUAN SAPROFITIK ISOLAT JAMUR UPAS DARI TEGAKAN CEMARA UDANG - , MOHAMAD RIZKY H, Dr. Sri Rahayu, MP ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Casuarina equisetifolia cultivation is an effort to rehabilitate the coastal area. C. equsetifolia has function as the wind break, but monoculture stands will increase the growth potential of Corticium salmonicolor. Information on morphological characteristics and saprophytic potency of C. salmonicolor are still limited. This research aims to find out C. salmonicolor isolates characteristics from in vitro C. equisetifolia stands and evaluate saprophytic potency of C. salmonicolor on C. equisetifolia twigs originated from vegetative and generative materials. C. salmonicolor isolates was taken from C. equisetifolia stands in Samas Coast, Bantul, Kwaru Coast, Bantul, and Lembupurwo Coast, Kebumen. Observation were conducted on 1) C. salmonicolor morphology from field and its microscopic appearance, 2) the growth of C. salmonicolor isolates in different humidity, temperature and light intensity, and 3) saphrophytic potency of C. salmonicolor on sterilized twig of C. equisetifolia size 6 x 0,5-1 cm originated from generative and vegetative materials. The research design used was the Completely Randomized Design (CRD). C. salmonicolor isolates growing in C. equisetifolia stands in the coastal area have better characteristics growth in high humidity (>80%), temperature 25-27 Â°C and light intensity 107-111 Lux. C. salmonicolor mycelia growth on C. equsetifolia twig from generative and vegetative materials showed that saprophytics potency of C. salmonicolor isolates from Samas and Kwaru Coast were higher than isolate from Lembupurwo Coast.